Síntese de nanopartículas de magnetita via decomposição térmica em meio não-aquoso - Costa, Tharsia Cristiany de Carvalho (2013)
This work aims at obtaining nanoparticles of iron oxide, the magnetite one (Fe3O4), via synthesis by thermal decomposition through polyol. Thus, two routes were evaluated: a simple decomposition route assisted by reflux and a hydrothermal route both without synthetic air atmosphere using a synthesis temperature of 260ºC. In this work observed the influence of the observe of surfactants which are generally applied in the synthesis of iron oxide nanoparticles decreasing cluster areas. Further, was observed pure magnetite phase without secondary phases generally found in the iron oxide synthesis, a better control of crystallite size, morphology, crystal structure and magnetic behavior. Finally, the introduction of hydroxyl groups on the nanoparticles surface was analyzed besides its employment in the polymer production with OH radicals. The obtained materials were characterized by XRD, DLS, VSM, TEM, TG and DSC analyses. The results for the magnetite obtainment with a particle size greater than 5 nm and smaller than 11 nm, well defined morphology and good magnetic properties with superparamagnetic behavior. The reflux synthesis was more efficient in the deposition of the hydroxyl groups on the nanoparticles surface